The Influence of Competence, Independence, and Information Technology on Audit Quality with Organizational Commitment Moderation - Nuzmika Putri; Lilis Ardini; Kurnia Kurnia (Eduvest - Journal of Universal Studies, 2025)
This study examines the effect of competence, independence, and information technology on audit quality. Besides, it also examines the impact of competence, independence, and information technology on audit quality; with organizational commitment as a moderating variable. Furthermore, the population consists of 150 auditors of Financial Audit Board (BPK) representatives, East Java province who are listed. The data collection technique used total sampling. In line with that, 40 respondents were chosen as the samples. Moreover, the data analysis technique used Partial Least Square (PLS) with Structured Equation Modelling (SEM). As a result, it shows that competence, independence, and information technology have a positive effect on the audit quality of auditors of BPK representatives, East Java province who are listed. On the other hand, organizational commitment cannot moderate the effect of competence, independence, and information technology on the audit quality auditors of Financial Audit Board (BPK) representatives, East Java province who are listed.